Use of MOCAF flour as raw material for healthy and hygienic lakar crackers in N&N MSMEs - Muhaimin Muhaimin; Anis Yohana Chaerunisaa; Tiana Milanda; Intan Timur Maisyarah; Uce Lestari; Mayang Kusuma Dewi; Lia Mardiana; Karina Erlianti (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2023)
In the vicinity of NN Micro, Small, and Medium Enterprises (MSME) in Jatiroke Village, Sumedang, West Java, cassava plantations abound, yet their harvest is often undervalued and sold at low prices. To enhance economic value, cassava from Jatiroke Village is now being processed into Modified Cassava Flour (MOCAF) for use as a primary ingredient in lakar cracker production at NN MSME. Previously, wheat and tapioca flours were sourced from the market for cracker production. The objective of this Community Partnership Empowerment (CPE) initiative is to replace wheat flour with locally processed MOCAF, diversifying food ingredient sources using available resources. MOCAF is not only gluten-free but is also deemed safe for consumption, especially for those with autoimmune diseases, memory loss, and autism. The CPE program includes training on MOCAF flour production and hands-on experience in making lakar crackers with MOCAF as a core ingredient. This comprehensive effort aims to promote NN MSME's growth by incorporating innovative technology for the production of healthy and hygienic crackers, thereby benefiting public health, particularly individuals with autoimmune conditions. This strategic shift not only holds economic promise but also contributes to the well-being of the community.